TEKNOLOGI ALAT-ALAT KESEHATAN DAN KESELAMATAN KERJA (K3) (Literatur Review) - Fitri Nur Amalia; Tedi Irawan; Lili Oktaviani; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2023)
Occupational Health and Safety (K3) is defined as a science and its application in an effort to prevent accidents, fires, explosions, disease contamination, and so on. K3 contains Personal Protective Equipment (PPE), which is mandatory equipment that is used when working according to the hazards and risks of work to maintain the safety of the workers themselves and other people in the workplace. The use of PPE is adjusted to the profession or work performed. In general, PPE consists of protective equipment for the head, eyes and face, hearing, breathing, hands, feet, height and body.